(untitled) (Journal of Music Research Online, 2022)
The feminist research endeavour in music, among other political agenda, aimed to improve the visibility of women composers in the concert hall. In the 1990s, a wealth of research became available. In the first decade of the twenty-first century, however, all that had been previously achieved faded away: scholars seemed to lose interest in women’s music destined for the concert hall. Any number of reasons might be given, including the resistance of some researchers to aligning themselves with music that emerges from the elitist concert hall tradition and/or to the threat of extinction facing classical music writ large. Overriding any single factor, however, as I will argue in this paper, is the static way in which the research on women’s ‘new’ music has been conducted. The paradox of this work is its unavoidable replication of the past by envisioning the future from the standpoint of the present. Such work inevitably reinforces the status quo. While acknowledging that it is impossible to generate new ways of thinking that are entirely disconnected from the old, I will draw on Deleuze, and feminist-Deleuzian scholarship, to offer new possibilities for thought and action. In particular, I will explore the power of the ‘virtual’, suggesting that some women’s music might be understood as a ‘becoming-imperceptible’, in Braidotti’s interpretation, as the process of ‘becoming-other-than-itself’, suspended between the no-longer and the not-yet.